2014
DOI: 10.1128/genomea.00295-14
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of a Virulent Streptococcus agalactiae Strain, 138P, Isolated from Diseased Nile Tilapia

Abstract: Streptococcus agalactiae strain 138P was isolated from the kidney of diseased Nile tilapia in Idaho during a 2007 streptococcal disease outbreak. The full genome sequence of S. agalactiae 138P is 1,838,701 bp. The availability of this genome will allow comparative genomics analysis to identify genes for antigen discovery and vaccine development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Both ST-260 and ST-261 have previously been identified as infecting aquatic animals. ST-260 isolates have been isolated from tilapia in Brazil and Costa Rica and occupy clonal complex 552 (CC552), along with ST-552 and ST-553 strains also isolated from tilapia in Latin America (27), ST-261 has been isolated from tilapia in the United States, China, Ghana, and Israel (9,13,30).…”
Section: Resultsmentioning
confidence: 99%
“…Both ST-260 and ST-261 have previously been identified as infecting aquatic animals. ST-260 isolates have been isolated from tilapia in Brazil and Costa Rica and occupy clonal complex 552 (CC552), along with ST-552 and ST-553 strains also isolated from tilapia in Latin America (27), ST-261 has been isolated from tilapia in the United States, China, Ghana, and Israel (9,13,30).…”
Section: Resultsmentioning
confidence: 99%
“…; Zhang et al . ; Pridgeon and Zhang ). In Thailand, outbreaks of streptococcosis in tilapia cultures commonly occur between April and September, when the temperature increases and the water quality decreases.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular serotyping indicated that all Queensland and Honduras aquatic strains belong to serotype Ib but Queensland isolates belong to sequence type (ST)-261 while Honduras strains are ST-260. Both ST-260 and ST-261 have been identified infecting aquatic animals previously with ST-260 isolates found in tilapia from Brazil and Costa Rica and occupying clonal complex (CC) 552 along with ST-552 and ST-553 strains also isolated from tilapia in Latin America (27), whilst ST-261 has been isolated from tilapia in USA, China, Ghana and Israel (9, 13, 30).…”
Section: Resultsmentioning
confidence: 99%